Elaboración de galletas integrales enriquecidas con quinua (chenopodium quinoa L.) y pasta de chocho (lupinus mutabilis sweet) edulcoradas con panela - Ocampo Ventura, Juan (2015)
The present study was conducted to obtain crackers enriched flour quinoa (Chenopodium quinoa L.) pulp lupine (Lupinus mutabilis Sweet) and sweetened with granulated panela, with optimal sensory and nutritional characteristics of the cookie, for it organoleptic characteristics, of the final product on the study factors was evaluated raised; and, proximate analysis (iron), and microbiological. There is also information about the most outstanding nutritional characteristics, pros and cons of each of these commodities. Technological parameters obtained are also shown in the development of comprehensive cookie. The grain of pearl Quinoa was of the city of Trujillo (region of La Libertad), the Chocho debittering district Lámud (Amazon region) and panela from the district of Lamas (region of San Martín), which was purchased from industrial company Oro Verde SAC The proximate analysis of quinoa flour reported a percentage of humidity 15%, 9.5% protein, 5.5% fat, 3.80% fiber, carbohydrates 63.1 %, Ash 3.10%, lron 41 ppm, with a bulk density of 0.59 g I cm3, pH 6.14 andan acidity of 0.1 % calculated as sulfuric a cid. The proximate analysis paste Chocho reporta percentage of humidity 75%, 48.5% Protein, Fat 23.50%, 10.25% fiber, carbohydrates 15%, Ash 2.75%, lron 90 ppm, pH 6.15 and an acidity of 0.03% expressed as sulfuric acid and iron determination granulated sugar that was 28 ppm. Obtaining comprehensive quinoa flour, pasta obtaining comprehensive chocho and processing Cookie: The following steps were developed. The method used to prepare the cookie was cremated method (Creaming Up), and operations that followed were: Formulation, Heavy, Smoothie I Mixed (1 st, 2nd Stage y3ra), Molded, Rest, Baking and Cooling .Where the factors studied were: Factor A three types of flour mixes (Factor Three types of flour mixes (A1 = 30-32% Wheat, 24-22.5% Quinoa, 24-22.5% Chocho, A2 = 40-37% Wheat, 20-19% Quinoa, 20-19% Chocho and A3 = 48-45% Wheat, 16-15% Quinoa, 16-15% Chocho), the factor 8 two percentages of panela (81 = 82 = 20% and 25%) and Factor C after a rebound baked ata temperatura of 100 º C (C1 = 28 min. and C2 = 30 min.). Combination of factors we obtained 12 treatments. For proximate analysis cookie it was determinad through the method recommended by AOAC (1990) .and the color, aroma, crispness and flavor through the nine-point hedonic scale sensory attributes. The data obtained were analyzed with the statistical program "SAS" for Complete Randomized Design. The energy analysis of physicochemical and better treatment selected T11 (45% wheat, 15% Quinoa, 15% Chocho, 25% Panela, baked for 28 minutes at 100 º C) was: moisture 1.5%, Protein 12%, Fat 5.5%, ash 4%, fiber 11.5%, 65.5% Carbohydrates, lron 1.5ppm, energy 359.5kcal/100g and microbiological quality is within the standards allowed by national standards. This product may be intended for wide consumption and particularly for that sector of the population that requires special nutritional content in their diet because excels in protein and fiber.